Methanosphaera stadtmanae induces a type IV hypersensitivity response in a mouse model of airway inflammation. Issue 7 (31st March 2017) - Bernatchez, Emilie; Gold, Matthew J.; Langlois, Anick; Blais‐Lecours, Pascale; Boucher, Magali; Duchaine, Caroline; Marsolais, David; McNagny, Kelly M.; Blanchet, Marie‐Renée
Abstract: Despite improved awareness of work‐related diseases and preventive measures, many workers are still at high risk of developing occupational hypersensitivity airway diseases. This stems from a lack of knowledge of bioaerosol composition and their potential effects on human health. Recently, archaea species were identified in bioaerosols, raising the possibility that they play a major role in exposure‐related pathology. Specifically, Methanosphaera stadtmanae (MSS) and Methanobrevibacter smithii (MBS) are found in high concentrations in agricultural environments and respiratory exposure to crude extract demonstrates immunomodulatory activity in mice. Nevertheless, our knowledge of the specific impact of methanogens exposure on airway immunity and their potential to induce airway hypersensitivity responses in workers remains scant. Analysis of the lung mucosal response to methanogen crude extracts in mice demonstrated that MSS and MBS predominantly induced TH 17 airway inflammation, typical of a type IV hypersensitivity response. Furthermore, the response to MSS was associated with antigen‐specific IgG1 and IgG2a production. However, despite the presence of eosinophils after MSS exposure, only a weak TH 2 response and no airway hyperresponsiveness were observed. Finally, using eosinophil and mast cell‐deficient mice, we confirmed that these cells are dispensable for the TH 17 response to MSS, although eosinophils likely contribute to the exacerbation of inflammatory processes induced by MSS crude extract exposure. We conclude that, as MSS induces a clear type IV hypersensitivity lung response, it has the potential to be harmful to workers frequently exposed to this methanogen, and that preventive measures should be taken to avoid chronic hypersensitivity disease development in workers. Abstract : Using a mouse model of lung exposure to archaeal crude extracts, we characterized the type of hypersensitivity response induced by methanogen ( Methanosphaera stadtmanae (MSS) and Methanobrevibacter smithii (MBS)) exposure. We demonstrate that both species induce predominantly a TH 17 lung mucosal response, typical of a type IV hypersensitivity response and, using genetically modified mice, we show that while eosinophils are dispensable for MSS‐induced airway hypersensitivity, they likely contribute to exacerbate airway inflammation upon exposure to this antigen. We conclude that exposure to methanogen bioaerosols, especially MSS, should be limited, if not prevented.